2016
DOI: 10.1021/acsmacrolett.5b00857
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine-Containing HPMA Copolymers as Polymeric Inhibitors of Cancer Cell Migration Mediated by the CXCR4/SDF-1 Chemokine Axis

Abstract: Chloroquine-containing HPMA copolymers (pCQs) were synthesized for the first time by copolymerization of methacryloylated hydroxychloroquine and HPMA. The copolymers showed lower cytotoxicity when compared with hydroxychloroquine. Treatment of cancer cells with pCQ resulted in decreased surface expression of chemokine receptor CXCR4. The pCQ copolymers showed effective inhibition of CXCR4/SDF1-mediated cancer cell migration that was fully comparable with a commercial small-molecule CXCR4 antagonist AMD3100. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…We recently reported synthesis of pCQ (Scheme 1) as a potential polymeric drug that takes advantage of the multivalency effect to enhance the ability of CQ to inhibit CXCR4-mediated invasion of lymphoma and leukemia cells [25]. We found that pCQ with 10 and 16.7 mol% of MA-CQ exhibited the most favorable activity profile in leukemia and lymphoma cells in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported synthesis of pCQ (Scheme 1) as a potential polymeric drug that takes advantage of the multivalency effect to enhance the ability of CQ to inhibit CXCR4-mediated invasion of lymphoma and leukemia cells [25]. We found that pCQ with 10 and 16.7 mol% of MA-CQ exhibited the most favorable activity profile in leukemia and lymphoma cells in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…This inhibition of CXCL12 binding then prevents CXCR4 receptor internalization and suppresses activation of the related downstream signaling cascades. CQ and HCQ on the other hand, appear to promote internalization of the surface CXCR4 receptors and their sequestration in the lysosomes, which then makes the receptors inaccessible for binding with extracellular CXCL12 chemokine molecules [15, 25]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CQ inhibited CXCR4‐mediated invasion and proliferation of pancreatic cancer cells and improved overall survival of tumor‐bearing mice when combined with gemcitabine . More recently, our group developed CQ‐containing N‐(2‐hydroxypropyl)methacrylamide (HPMA) copolymers, which achieved greatly enhanced inhibition activity against cancer cell migration and tumor metastasis in vivo …”
Section: Introductionmentioning
confidence: 99%
“…53, 54 However, the HPMA-based polymer demonstrated only limited ability to inhibit autophagy, one of the main mechanisms by which HCQ exerts its therapeutic actions. This led us to investigate other HCQ-modified polymers that better retained the autophagy inhibitory properties of HCQ for improved anticancer activity.…”
Section: Introductionmentioning
confidence: 99%